Effects of 2'-deoxy-2'-azidocytidine on polyoma virus DNA replication: evidence for rolling circle-type mechanism. - Bjursell, G (1978)
Rolling circle-type molecules were found in polyoma virus-infected cells after inhibition of DNA synthesis with 2'-deoxy-2'-azidocytidine. The circular DNA molecules were always relaxed and of polyoma length. Most of the attached tails were less than two times the length of the polyoma genome, but tails with a length of up to 4.75 times the genome were also found. After cleavage of the total pool of replicating molecules with either endo R.EcoRI or endo R.BamI, Y-shaped molecules with replicated portions of various lengths were generated from rolling circle-type molecules. Moreover, after cleavage, Y-shaped molecules with three unequal arms were found, which could be explained as derived from the tail in rolling circle-type molecules starting from the normal origin, i.e., 29% from the endo R.EcoRI cleavage site. Rolling circle-type molecules were also found during a normal, noninhibited infection cycle. In such cells, a relatively higher frequency of rolling circle-type molecules was observed late during infection. Compared with control cultures, cultures inhibited with 2'-deoxy-2'-azidocytidine showed a greater amount of rolling circle-type molecules relative to normal replicative intermediates. 2'-Deoxy-2'-azidocytidine has previously been shown to inhibit the initiation of new rounds of replication; thus, the result obtained here indicates that a rolling circle-type mechanism is independent of the reinitiation of DNA synthesis.